Caval umbrella causing obstructive uropathy. Issue 846 (April 1996) - Flanagan, D.; Creasy, T.; Chataway, F.; Kerr, D.
Abstract : A 49-year-old woman had a vena caval filters inserted having suffered multiple pulmonary emboli and a large upper gastrointestinal bleed. She re-presented five years later with loin pain and obstructive uropathy. She was found to have a right pelvi-ureteric obstruction due to inferior vena caval wall perforation from the vena caval filter.